Dasyphyllum diamantinense (Asteraceae, Barnadesioideae): a new species from the Chapada Diamantina, Bahia State, Brazil - Saavedra, Mariana Machado; Monge, Marcelo; Guimarães, Elsie Franklin (Phytotaxa, 2014)
Dasyphyllum diamantinense is a new species endemic to the Chapada Diamantina Mountains in the northern section of the Espinhaço Range, in Bahia State, Brazil, which grows in rocky fields, forests and savannas, and on inselbergs. The new taxon is morphologically similar to Dasyphyllum leptacanthum. Affinities and diagnostic characters are discussed, and illustrations and a map are provided.